Answer:
c. 2 OH⁻(aq) + 2 H⁺(aq) ⇒ 2 H₂O(l)
Explanation:
Step 1: Write the molecular equation
The molecular equation includes all the molecular species.
H₂A(aq) + 2 NaOH(aq) ⇒ Na₂A(aq) + 2 H₂O(l)
Step 2: Write the complete ionic equation
The complete ionic equation includes all the ions and the molecular species.
2 H⁺(aq) + A²⁻(aq) + 2 Na⁺(aq) + 2 OH⁻(aq) ⇒ 2 Na⁺(aq) + A²⁻(aq) + 2 H₂O(l)
Step 3: Write the net ionic equation
The net ionic equation includes only the ions that participate in the reaction and the molecular species.
2 OH⁻(aq) + 2 H⁺(aq) ⇒ 2 H₂O(l)